Capital Adequacy and Bank Stability: A Panel ARDL Analysis of Selected Listed Deposit Money Banks in Nigeria - Müller, Christian; Aondoaseer , Moses (Ayden International Journal of Banking, Finance and Technology, 2024)
This study examined to examine the effects of capital adequacy on the stability of quoted banks in Nigeria from 2010 to 2022. The study used a panel of eight banks in Nigeria, Access, First Bank, FCMB, Fidelity Bank, GTB, UBA, Union Bank of Nigeria and Zenith bank, all listed in the Nigerian Stock Exchange. The study was based on the expos fato research design and used secondary data sourced from the annual reports of the sampled banks. The study examined a number of significant capital adequacy variables that are difficult to neglect when trying to understudy the effects of capital adequacy. These variables include bank capital to total credit ratio (BCTCA), loan to deposit ratio (LDR), debt to equity ratio (DER) and risk weighted asset (RWA). The study adopted the Panel Autoregressive Distributed Lag (PARDL) technique to estimate our parameters. From the study’s findings, it can be concluded that loan to deposit ratio (LDR) and debt to equity ratio (DER) have significant inverse effect on bank stability in Nigeria, while bank capital to total credit ratio (BCTCA) and risk weighted asset (RWA) have significant positive effect on the stability in Nigerian banks. So, in summary, increasing or reducing the capital adequacy indicators matter to bank stability in Nigeria. Based on the findings and conclusions, the study proffers the following recommendations: that Nigerian banks that desire to improve their stability should reduce the ratio of loan to deposit and debt to equity, but increase bank capitalization to total credit ratio and their risk-weighted assets.